2012
DOI: 10.1128/jcm.06791-11
|View full text |Cite
|
Sign up to set email alerts
|

A New and Highly Divergent Enterocytozoon bieneusi Genotype Isolated from a Renal Transplant Recipient

Abstract: A 49-year-old renal transplant recipient was admitted to our hospital due to abundant liquid diarrhea and dehydration. Parasitological investigations, including genotyping, led to the diagnosis of intestinal microsporidiosis due to a new and highly divergent internal transcribed spacer (ITS) genotype of Enterocytozoon bieneusi. The potential route of transmission through horse stools is discussed. CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The finding of infection of E. bieneusi is in accordance with the previously reported series of patients with RT. [6][7][8][9][10][11]17] Therefore, E. bieneusi is the common species causing intestinal microsporidiosis in RT The present report is the first largest case-control study on microsporidia in renal transplant recipient. To the best of our knowledge, only about 31 cases and a retrospective study on intestinal microsporidiosis in RT recipients have been reported till date.…”
Section: Treatment and Follow-upmentioning
confidence: 64%
See 3 more Smart Citations
“…The finding of infection of E. bieneusi is in accordance with the previously reported series of patients with RT. [6][7][8][9][10][11]17] Therefore, E. bieneusi is the common species causing intestinal microsporidiosis in RT The present report is the first largest case-control study on microsporidia in renal transplant recipient. To the best of our knowledge, only about 31 cases and a retrospective study on intestinal microsporidiosis in RT recipients have been reported till date.…”
Section: Treatment and Follow-upmentioning
confidence: 64%
“…Similarly, mean age of microsporidia infected RT recipients as reported in different cases and retrospective study was 45.8 ± 11 and 44 years, respectively. [5][6][7][8][9][10][11][12]17] Since transplant recipients with younger age are at an increased risk of infection with microsporidia, such patients should be thoroughly investigated for microsporidiosis. Chronic diarrhoea is a common clinical presentation of immunocompromised patients infected with microsporidia.…”
Section: Treatment and Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, SOT recipients are considered as a new risk group for microsporidiosis. To date, only 74 cases have been reported in SOT (Table ) (, and the present report), mainly in renal transplant recipients ( n = 53), in whom the intensity of symptoms is not proportionally related to CD 4 + count (unlike in the HIV‐positive population) . Within this limited cohort, FK506, mycophenolate mofetil, and CsA have been used mainly as immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 81%